2016
DOI: 10.1155/2016/6315846
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Extracorporeal Shock Wave Therapy for Insertional Achilles Tendinopathy with and without Haglund’s Deformity

Abstract: Purpose. To compare the results of extracorporeal shock wave therapy (ESWT) for insertional Achilles tendinopathy (IAT) with or without Haglund's deformity. Methods. Between September 2014 and May 2015, all patients who underwent ESWT were retrospectively enrolled in this study. A total of 67 patients were available for follow-up and assigned into nondeformtiy group (n = 37) and deformtiy group (n = 30). Clinical outcomes were evaluated by VISA-A Score and 6-point Likert scale. Results. The VISA-A score increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The presence of Haglund’s deformity negatively affects the outcome of ESWT in patients with IAT 31. Notarnicola et al reported the outcomes of the use of ESWT compared with High Energy Laser Therapy (CHELT), both followed by a protocol of eccentric exercises and stretching.…”
Section: Management Of Iatmentioning
confidence: 99%
“…The presence of Haglund’s deformity negatively affects the outcome of ESWT in patients with IAT 31. Notarnicola et al reported the outcomes of the use of ESWT compared with High Energy Laser Therapy (CHELT), both followed by a protocol of eccentric exercises and stretching.…”
Section: Management Of Iatmentioning
confidence: 99%
“…For plantar fasciitis, ESWT has shown to be more effective than RSW (12). We reviewed several studies on SW for Achilles tendinopathy (table I A-D); seven previous studies (13,14,15,16,17,18,19) showed significant improvement in patients with Achilles tendinopathy treated with RSW. Five of those seven studies (13,14,15,16,19) had control groups that did not receive shockwave treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This was not considered statistically significant, given the sample size. (18). There was no control group.…”
Section: Gerdesmeyer 2017mentioning
confidence: 99%
“…A four-month duration was selected as the eligibility criterion by Costa et al [23], while others considered patients who had been suffering for six months [6,7,17,19,20,22,28,29,[34][35][36]. Santamato et al [33] and Lynen et al [27] used shorter eligibility periods, i.e., 4 and 6 weeks, respectively, while several authors did not specify the duration of Achilles tendinopathy symptoms at all [26,32,38]. Regarding acute tendinopathy, Ciccotti et al [41] emphasized that although patients describe the pain as acute, the degenerative character of the dysfunction indicates that the tendon's adaptation to tensile overloading has been impaired long before symptom occurrence.…”
Section: Achilles Tendon Dysfunction Characteristics a Chronicmentioning
confidence: 99%